Doubtful use of placebo following placebo in recent controlled trials of lasmiditan and ubrogepant for the treatment of migraine attacks - Tfelt-Hansen, Peer; Jørgensen, Karsten; Diener, Hans-Christoph (Cephalalgia, 2022)
Purpose In four large controlled trials with lasmiditan and ubrogepant placebo was administered in the first step to demonstrate an effect on migraine attack. In the same trials the investigators also asked the question: is a second dose of the drug effective in non-responders to the first dose? In this phase patients who received placebo in the first phase of the trial again after 2 hours received another dose of placebo. Conclusion To be ethical, clinical research requires balancing rigorous science with the protection of human subjects; and it is, in our view, questionable whether placebo was used with “scientific rigor” in the second step of these trials, and this design is not recommended.